A young man with typical STEMI presentation: A case of myocarditis A Cardiac MRI Diagnosis - Saskia D Handari; Joseph B Selvanayagam (Jurnal Kardiologi Indonesia, 2010)
A 19 years old man, originated from Kongo, presented to a hospital with acute chest pain since several hours before admission. The pain was sharp in quality, distributed in the middle of left chest, not exercise related and not radiating. Although there were times in which the patient felt the pain was downgrading, it did not totally fade away. The patient was non-smoker with no risk factors of diabetic, hypertension and dyslipidaemia. He was oriented with temperature of 38.5 C, pulse was 110 tpm, blood pressure was 128/85 mmHg with fast and shallow respiration at the rate of 32 tpm. S1/S2 normal, no additional sound and significant murmur detected. Apart from minimal harsh respiratory sound at the basis of left lung, the examinations of JVP, lung and abdomen were unremarkable. Since 7 days before admission, the patient suffered cough, runny nose and throat pain with feverish but did not seek treatment for it. ECG showed sinus tachycardia with ST-elevation in inferior and anterolateral leads. Elevated cardiac enzymes CKMB 32 and Trop T 1,86.